SEROLOGICAL AND IMMUNOLOGICAL STUDY OF A FOOT - AND - MOUTH DISEASE VIRUS STRAIN, TYPE 0,WHICH CAUSED AN EPIZOOTIC IN EVROS DEPARTMENT IN 1972 - ΜΠΡΟΒΑΣ, Δ.; ΠΑΠΠΟΥΣ, Χ. (Journal of the Hellenic Veterinary Medical Society, 1974)
The Foot — and — Mouth Disease (FMD) virus strain, type O, which caused an epizootic in cattle of Peplos community in the Evros Department, near the turkish border, at the end of November 1972 (Strain Ο Peplos/72) was compared with the Dutch strain Ox used for the production of stock vaccines. Besides the strain Ο Peplos/72 was compared serologically with the strain Ο Ferrai/67 which had previously caused an epizootic in the same area. For the serological study the microtechnique of complement fixation described by Darbyshire, Hedger and Ann Arrowsmith and modified by Forman was applied. The value (R) between the strain O, Peoplos/72 and Ο Holland was 30%. The respective value between the strains Ο Peplos/72 and Ο Ferrai/67 was 50%. The immunological study was carried out on guinea - pigs using experimental vaccines prepared from virus grown on BHK cells. The immunological relationship between the stains Ο Peplos/72 and O, Holland was 24%. According to the biomathematical system of dominance (D) proposed by Stellmann et alt. the strain Ο Peplos/72 appears to dominate both over O, Holland and 0 Ferrai 67 giving values D 1.183 and 1.424 respectively. The above data and the observations in the field justifie the use of the strain Ο Peplos 72 for vaccine production.